Performance of rice blast resistance genes in multi-environment tests in India - M. SRINIVASPRASAD and R. SRIDHAR, K. MURALIDHARAN*, D. KRISHNAVENI, G.S. LAHA, C.S. REDDY (Indian Phytopathology, 2004)
Rice genotypes carrying resistance genes to blast disease were evaluated in multi-environment tests (METs). Tadukan carrying resistance gene Pi-ta showed small lesions infecting